2023
DOI: 10.1371/journal.pone.0282816
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ingredients: Supramolecular structure of lipid droplets in infant formula affects metabolic and brain function in mouse models

Abstract: Human milk beneficially affects infant growth and brain development. The supramolecular structure of lipid globules in human milk i.e., large lipid globules covered by the milk fat globule membrane, is believed to contribute to this effect, in addition to the supply of functional ingredients. Three preclinical (mouse) experiments were performed to study the effects of infant formula mimicking the supramolecular structure of human milk lipid globules on brain and metabolic health outcomes. From postnatal day 16… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…It is hypothesized that differences in bioavailability of these components to the developing brain early in life may contribute to infant neurocognitive development (7). This idea is supported by a recent series of preclinical studies in mice demonstrating IF with large lipid droplets coated by PL promote n-3 LCPUFA accumulation in brain tissue and improve later in life cognitive function compared to IF with small lipid droplets and with PL present as added ingredient (21). Interestingly, the mere addition of dairy lipids and/or MFGM components to IF does not lead to structural properties of lipids similar to HM (68), nor does it appear to bring digestion and absorption kinetics closer to that of HM (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that differences in bioavailability of these components to the developing brain early in life may contribute to infant neurocognitive development (7). This idea is supported by a recent series of preclinical studies in mice demonstrating IF with large lipid droplets coated by PL promote n-3 LCPUFA accumulation in brain tissue and improve later in life cognitive function compared to IF with small lipid droplets and with PL present as added ingredient (21). Interestingly, the mere addition of dairy lipids and/or MFGM components to IF does not lead to structural properties of lipids similar to HM (68), nor does it appear to bring digestion and absorption kinetics closer to that of HM (69).…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical experiments using mouse models, early life exposure to Concept compared to Standard IF resulted in long term improvement in metabolic health and neurocognitive outcomes ( 19 21 ). In a randomized, controlled trial (Dutch Trial Register; NTR3683), we demonstrated that a Concept IF with dairy lipids and comprising large lipid droplets coated by (bovine MFGM derived) PL supported adequate growth and was safe and well-tolerated in healthy term infants ( 22 ).…”
Section: Introductionmentioning
confidence: 99%